Factors Associated for Caesarean Section among Mothers Attending in Teaching Hospital, Chitwan - Poudel, Indira Adhikari; Bhattarai, B; Dhakal, P (Journal of Manmohan Memorial Institute of Health Sciences, 2020)
Correction: The page numbers were changed from 57-67 to 39-49 on 31/08/2020. Background: Cesarean section (CS) rate has increased rapidly over the past two decades in world. It is serious concern for public health experts globally. Various medical and non-medical factors, such as maternal socio-demographics, are found to be responsible for this upsurge. Like in other countries, the rate of caesarean sections has increased in Nepal as well. Therefore, there is a need to investigate the factors behind this increase. Objectives: To identify the factors associate for caesarean section among mothers attending at teaching hospital, Chitwan Methods: A cross sectional analytical study was conducted using total enumerative sampling technique in the maternity ward of Chitwan Medical College Teaching Hospital. Interview was done with closed ended Questionnaire for data collection, a total number of 139 mothers after 24 hours cesarean section (CS). Results: The study shows that, nearly three- quarters (71.2%) of CS were performed as an emergency. There are mainly fetal, maternal and placental indication for cesarean section. The most frequent indications were: previous cesarean section (22.3%), thick Meconium stained liquor (12.2%), fetal distress (10.6%) and oligohydramnios (7.2%).